Human security under climate stress: environmental peacebuilding pathways in Somalia - Adan, Mohamed Yusuf (Frontiers in Political Science, 2025)
IntroductionSomalia provides a critical case for examining how climate change undermines human security and peace in fragile states. Climate-related environmental stress continues to intensify resource pressures, displacement, and governance challenges, shaping pathways toward instability.MethodsThe study applies qualitative content analysis using academic literature, United Nations and NGO reports, and national policy documents. It examines three interconnected mechanisms through which climate stress influences insecurity: inter-clan competition over land and water, tensions between displaced and host communities, and the exploitation of livelihood vulnerabilities by armed groups.ResultsFindings show that climate change acts as a threat multiplier, heightening resource disputes, displacement pressures, and institutional fragility. These dynamics collectively amplify economic, community, and political insecurity. The study develops the Environmental Peacebuilding Pathways Framework to illustrate how conflict-sensitive climate adaptation can strengthen resilience and cooperation.DiscussionThe research contributes theoretically by linking human security and environmental peacebuilding perspectives, and empirically by situating Somalia within wider climate-security debates. Practically, it highlights the importance of integrating peacebuilding approaches into national and local climate adaptation strategies in line with Sustainable Development Goal 13.